Impact of assimilating temperature and salinity measurements by animal‐borne sensors on FOAM ocean model fields. (9th September 2015) - Carse, Fiona; Martin, Matthew J.; Sellar, Alistair; Blockley, Edward W.
Abstract : Temperature and salinity profiles are being obtained from instrumented marine mammals in near real‐time. The mammals, mostly elephant seals, sample to depths of up to 2000 m in high‐latitude regions where there are very few other in situ observations. This study investigates the impact of mammal temperature and salinity observations on the UK Met Office's global ocean forecasting model, focussing on impacts in the Southern Ocean region. Three reanalyses were performed, each assimilating a varying amount of seal data whilst holding all other conditions constant. Assimilation of both temperature and salinity profiles from mammals has a detrimental effect on the model's temperature and salinity fields due to a high bias in the salinity values. Restricting assimilation to temperature profiles only has benefits for both temperature and salinity fields in regions of the ocean where seals are sampling, improving root‐mean‐square error statistics by between 1 and 6% compared to the case where no mammal data were assimilated. In addition, the assimilation of seal temperature profiles alters the mixed‐layer depth and repositions and increases gradients of some fronts compared to the no‐seals case. Abstract : Marine mammals are gathering near real‐time oceanographic profiles in high latitude regions, including the Southern Ocean and Antarctica's continental shelf. These areas are currently under‐sampled by other observing networks. Data collected by species including Southern elephant seals ( Mirounga leonina, left) and Weddell seals ( Leptonychotes weddellii, right) provide ocean sections up to 2, 000 metres deep, as well as valuable measurements near and under the sea ice. In this paper, Carse et al. explore the impact of assimilating these new observations into the Met Office's daily global ocean forecast model.